Evaluación del desgaste de prótesis cerámicas de cadera recubiertas con DLC por triboadhesión parte II – pruebas de depósito y desgaste - Rodríguez Lelis, J. M.; Sosa G, W. E.; Ciénega Ramos, Mario (Revista Mexicana de Ingenieria Biomedica, 2006)
In this paper, the results of coating an aluminum oxide (Al2O3) femoral head of a hip prosthesis with DLC, diamond-like carbon, are presented. The triboadhesion coating process was carried out with the device designed by the authors. Here are also shown the wearing tests of the femoral head with and without coating. The wear resistance was evaluated through vibration signal analysis. The results showed that the prosthesis coated by the triboadhesion process exhibit a higher wear resistance than the one without coating.